Kuliah Kerja Nyata : Pengembangan Keterampilan Dasar Sepak Bola bagi Remaja Usia 12 Tahun di Desa Siwarak, Kecamatan Karangreja, Kabupaten Purbalingga: Pengabdian - Ahmad Syarif; Krisno (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity was carried out as part of the Community Service Program (KKN) of Universitas Ma’arif Nahdlatul Ulama Kebumen in Siwarak Village, Karangreja District, Purbalingga Regency. The main problem in this village is the lack of structured sports coaching despite having adequate infrastructure and high public interest. The program focuses on developing basic football skills for 12-year-old youth as a means of character building, improving physical fitness, and strengthening social solidarity. The implementation method includes field observation, training program preparation, and the execution of basic technique training (passing, dribbling, shooting, and ball control) conducted regularly. The results show an improvement in technical skills, awareness of healthy living, and active community participation. This program also increases the interest of the younger generation to develop sports talent and pursue higher education. This activity is expected to serve as a model for village sports development based on character education.